2010
DOI: 10.1021/la102721m
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Activity and Interfacial Shear Rheology of Native β-Lactoglobulin Monomers and Their Heat-Induced Fibers

Abstract: Interfacial properties of native β-lactoglobulin monomers and their heat-induced fibers, of two different lengths, were investigated at pH 2, through surface tension measurements at water-air and water-oil interfaces and interfacial shear rheology at the water-oil interface. The applied heat treatment generates a mixed system of fibers with unconverted monomers and hydrolyzed peptides. The surface tension of this system at the water-air interface decreased more rapidly than the surface tension of native monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
123
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 53 publications
11
123
0
Order By: Relevance
“…The exact extent of cleavage to peptides, formation of fibres and deamidation is very difficult to identify and quantify, therefore the bulk composition of the system being studied is at best only qualitatively understood. This type of issue makes even the simplest of experiments difficult to interpret, as in the study by Jung et al [14], where the observed interfacial tension kinetics could not be clearly explained. Second, the interfacial composition is even more difficult to characterize than that in the bulk.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The exact extent of cleavage to peptides, formation of fibres and deamidation is very difficult to identify and quantify, therefore the bulk composition of the system being studied is at best only qualitatively understood. This type of issue makes even the simplest of experiments difficult to interpret, as in the study by Jung et al [14], where the observed interfacial tension kinetics could not be clearly explained. Second, the interfacial composition is even more difficult to characterize than that in the bulk.…”
Section: Introductionmentioning
confidence: 96%
“…First, systems composed of natural components are often complex and difficult to characterize. For example, heat treatment of b-lactoglobulin at pH 2 to form fibres results in a mixed system of fibres, monomers, peptides and deamidated variants of each [14]. The exact extent of cleavage to peptides, formation of fibres and deamidation is very difficult to identify and quantify, therefore the bulk composition of the system being studied is at best only qualitatively understood.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we apply this paradigm to interfacial materials, specifically particle-stabilized drops and bubbles. These systems with high interfacial area have broad applicability from food formulation and processing (1,2), encapsulation (3,4), ultrasound medical technologies (5), to lowweight/high-strength materials (6). One of the key challenges in using solid stabilized emulsions and foams in applications is curtailing Ostwald ripening, which causes the growth/shrinkage of large/small bubbles and increased size heterogeneity (7).…”
mentioning
confidence: 99%
“…Jung and co-workers demonstrated that b-lactoglobulin monomers heated at pH 2 for 5 h at 90 C are more surface active than native monomers. 58 At very long times, further conformational rearrangements take place and a viscoelastic network is formed. [48][49][50] The formation of such network is confirmed by the dilatational frequency sweep after the 24 hours of adsorption.…”
mentioning
confidence: 99%